Older adults hearing screening strategies: a bibliometric review - Elisangela Rodrigues Brandão; Renan Dantas Aires Guimarães; Maria Júlia Galindo Soares; Hannalice Cavalcanti (Revista CEFAC, 2023)
ABSTRACT Purpose: to analyze the profile of publications on methods and instruments used to screen older adults hearing. Methods: the scientific production on older adults hearing screening methods, searching for articles published between 2016 and 2022. Data were collected from PubMed, Scopus, LILACS, Web of Science, and Google Scholar databases and the articles were categorized according to their year, study type, authors, and screening instrument. Data were also analyzed to suggest potential aspects to be addressed in future research in the area. Literature Review: altogether, 26 articles were found based on the eligibility criteria. Publications peaked in 2016, followed by 2020. Articles published in the United States predominated (18%), and HHIE-S (hearing handicap inventory for the elderly screening version) was the most used instrument; 90% of the publications were in English, and the most recurrent study type was cross-sectional, followed by instrument validation studies. Conclusion: the review points out the scarcity of scientific production on older adults hearing screening in both national and international research. The studies approached different populations, screening methods, hearing loss definitions, health systems, and public policies in the countries where they were conducted. Better methodologies must be implemented for future research in the area.